2018
DOI: 10.1186/s12951-018-0432-4
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanorods-conjugated TiO2 nanoclusters for the synergistic combination of phototherapeutic treatments of cancer cells

Abstract: BackgroundRecently, a combination of photodynamic therapy (PDT) and photothermal therapy (PTT) to generate reactive oxygen species (ROS) and heat to kill cancer cells, respectively has attracted considerable attention because it gives synergistic effects on the cancer treatment by utilizing the radiation of nontoxic low-energy photons such as long wavelength visible light and near IR (NIR) penetrating into subcutaneous region. For the effective combination of the phototherapies, various organic photosensitizer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Overall, aPDT should be taken into consideration because of their advantages, including the elimination of resistant microorganisms, few complications, improved selectivity and rapid time of action 18 . Even though locally applied aPDT avoids systemic adverse effects, high concentrations of PSs and high-energy doses of light are usually required to completely eliminate infectious bacteria 19 .…”
mentioning
confidence: 99%
“…Overall, aPDT should be taken into consideration because of their advantages, including the elimination of resistant microorganisms, few complications, improved selectivity and rapid time of action 18 . Even though locally applied aPDT avoids systemic adverse effects, high concentrations of PSs and high-energy doses of light are usually required to completely eliminate infectious bacteria 19 .…”
mentioning
confidence: 99%
“…A thermocouple was used for the measurement of photothermal temperature based on previous reports [23][24][25][29][30][31]. The thermocouple measurement used Delta OHM HD2128.2 T-type.…”
Section: Photothermal Measurementsmentioning
confidence: 99%
“…Recent advances in the multi-functional design of GNPs allow for the generation of localized heat in the proximity of cancer tissues and additionally allow the delivery of multiple desired drugs in a controlled and targeted manner. GNPs have many benefits that make them suitable for the photothermal treatment of tumor or cancer, because they can be delivered into the local tumor area while minimizing nonspecific distribution, activated via near-infrared (NIR) laser light, creating the ability to penetrate deep into biological tissues, and modulated to create multifaceted cancer photothermal therapy [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both PTT and PDT involve the utilization of light energy, and based on the local surface plasmon resonance (LSPR) of noble metal nanoparticles, the efficiency of PDT can be enhanced along with the photothermal effect, so PTT and PDT (PTT/PDT) synergistic treatment should achieve significant efficiency by ingenious design. Current studies have reported good efficiency of PTT/PDT synergistic therapy [17][18][19], but how does FA receptor-mediated endocytosis affect the amount and distribution of intracellular PTT/PDT nanodrugs are still lack.…”
Section: Introductionmentioning
confidence: 99%